3D printed microfluidic devices: enablers and barriers. Issue 11 (5th May 2016) - Waheed, Sidra; Cabot, Joan M.; Macdonald, Niall P.; Lewis, Trevor; Guijt, Rosanne M.; Paull, Brett; Breadmore, Michael C.
Abstract : 3D printing has the potential to significantly change the field of microfluidics. Abstract : 3D printing has the potential to significantly change the field of microfluidics. The ability to fabricate a complete microfluidic device in a single step from a computer model has obvious attractions, but it is the ability to create truly three dimensional structures that will provide new microfluidic capability that is challenging, if not impossible to make with existing approaches. This critical review covers the current state of 3D printing for microfluidics, focusing on the four most frequently used printing approaches: inkjet (i3DP), stereolithography (SLA), two photon polymerisation (2PP) and extrusion printing (focusing on fused deposition modeling). It discusses current achievements and limitations, and opportunities for advancement to reach 3D printing's full potential.